Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1981
DOI: 10.1021/ja00403a020
|View full text |Cite
|
Sign up to set email alerts
|

Solute-solvent interactions in perfluorocarbon solutions of oxygen. An NMR study

Abstract: Fluorinated compounds, including alkanes, alkenes, aromatics, amines, and cyclic and heterocyclic fluorochemicals, are studied as solvents of oxygen, using for this purpose the paramagnetic relaxation induced by the presence of molecular oxygen onto the I3C nuclei of neighboring solvent molecules in the solution. Relaxation data are expressed by the variation rates qx of relaxation rates TI-' per mole fraction of dissolved oxygen. A general correlation is found between the solubility of oxygen (in mole fractio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
80
0
1

Year Published

1988
1988
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(83 citation statements)
references
References 6 publications
(9 reference statements)
2
80
0
1
Order By: Relevance
“…Measurements are possible from anoxia to hyperbaric conditions, although the best precision is generally obtained below 10 mm Hg (166,167). This approach is conceptually different from the use of nitroimidazoles, which react chemically, leading to trapped adducts in hypoxic environments.…”
Section: Reporter Molecules For Mr Oximetrymentioning
confidence: 99%
“…Measurements are possible from anoxia to hyperbaric conditions, although the best precision is generally obtained below 10 mm Hg (166,167). This approach is conceptually different from the use of nitroimidazoles, which react chemically, leading to trapped adducts in hypoxic environments.…”
Section: Reporter Molecules For Mr Oximetrymentioning
confidence: 99%
“…s 01 (see Table 1). It is known that fluorinated organic compounds have exDecoupling of the 19 F spins of the solvent by strong RF [7] 50,000 …”
Section: Materials and Measurementsmentioning
confidence: 99%
“…However, a small contribution of 19 F to other if a Lorentzian spectral density is assumed. This is dipolar T 1 and T 2 relaxation of 13 C, not exceeding a few illustrated in Fig.…”
Section: Materials and Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…The solubility of oxygen (and gases in general) in perfluorocarbons and hydrofluorocarbons is three to ten times higher than observed in the parent hydrocarbons or in water (101,102). It was shown that a model of continuous diffusion of oxygen, that accounts for the T 1 and T 2 relaxation of benzene, fails in the case of HFB, leading to either impossibly short residence times for oxygen or impossibly small distance of closest approach between fluorine and oxygen (93).…”
Section: Measuring Pomentioning
confidence: 99%